2018
DOI: 10.1007/s00249-018-1338-7
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of crystalline and elemental composition of urinary stones with a history of bacterial infections: TXRF, XRPD and PCR-DGGE studies

Abstract: The aim of this study was to analyze the correlation between past bacterial infections and the type and chemical composition of urinary stones experienced by human patients. Bacteria have been recognized to contribute to urinary stones; however, the role of uropathogens in the development of specific stones has not been extensively investigated. The detection of past bacterial infection (eleven different bacterial species) in urinary stones from 83 patients was made on a DNA level using polymerase chain reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Recent advances in culture techniques and molecular biology, such as enhanced quantitative urine culture and 16S rRNA gene sequencing, have revealed that there are a variety of microorganisms that are not well identified in standard urine cultures [ 7 , 8 ]. The combination of DGGE and PCR allows the identification of the DNA of various microorganisms present in the biofilm of urinary calculi, which can help determine how they play a role in the formation of bladder calculi [ 9 , 20 ]. As a result of the combination of DGGE and PCR, P. aeruginosa was the most dominant within the biofilm of bladder calculi from each of the six rats with NB following SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in culture techniques and molecular biology, such as enhanced quantitative urine culture and 16S rRNA gene sequencing, have revealed that there are a variety of microorganisms that are not well identified in standard urine cultures [ 7 , 8 ]. The combination of DGGE and PCR allows the identification of the DNA of various microorganisms present in the biofilm of urinary calculi, which can help determine how they play a role in the formation of bladder calculi [ 9 , 20 ]. As a result of the combination of DGGE and PCR, P. aeruginosa was the most dominant within the biofilm of bladder calculi from each of the six rats with NB following SCI.…”
Section: Discussionmentioning
confidence: 99%
“…TXRF measurements were performed with the S 2 PICOFOX spectrometer (Bruker AXS Microanalysis GmbH). On the basis of [55,56] the characteristic X-rays were excited in the samples with the 30 W Mo-anode X-ray tube operated at 50 kV with an electron current of 0.6 mA. Fluorescence X-rays from the samples were detected by Peltier-cooled XFlash silicon drift detector (with an area 10 mm 2 ) having an energy resolution of approx.…”
Section: Total Reflection X-ray Fluorescence (Txrf) Techniquementioning
confidence: 99%
“…Fluorescence X-rays from the samples were detected by Peltier-cooled XFlash silicon drift detector (with an area 10 mm 2 ) having an energy resolution of approx. 160 eV at 100 kcps for Mn-Kα line [56]. The measurements were performed in the air.…”
Section: Total Reflection X-ray Fluorescence (Txrf) Techniquementioning
confidence: 99%
“…Pioneering work characterizing urinary stones with TXRF and XRD was done by Kubala‐Kuskus et al, 18–20 which however has not found its way to a more routine application. Using TXRF and X‐ray diffraction, the correlation between the chemical compositions of the urinary stones and the previous bacterial infections (eleven bacterial species) has been reported.…”
Section: Introductionmentioning
confidence: 99%